Relationship Between Innovation Barriers and Proactive Work Behavior in Selected Hotels in Nairobi City, Kenya. - Shirandula, Duncan (My University, 2015)
Proactive work behavior and innovation in hotels may bring about positive changes in work environment that may include improved quality products, increased efficiency, a cut on costs and a greater market share. Despite these benefits, hotels struggle to be proactive and innovative; but fail because of challenges brought about in particular by innovation barriers for instance governmental constraints, lack of competences, time and risks of failure. These innovation barriers may lessen employees’ personal initiative, ability to take charge, sell their issues and voice their views in the organization. The main objective of undertaking this study was to determine the relationship between innovation barriers and proactive work behaviour in selected hotels located in Nairobi city, Kenya. Specifically, the study tested the relationship between endogenous and exogenous innovation barriers and proactive work behaviour in the hotel industry. From the Kenya Bureau of Statistics report, gender diversity is a contemporary issue that may be associated with innovation process; therefore the study also tested the difference in proactive work behaviour between the male and female employees. The study employed a co-relational research design and was conducted in Nairobi city, Kenya. From a target population of 190 permanent front line employees, 127 formed the sample size for the study. Purposive sampling was used to select three five-star rated hotels in Nairobi, then employees in the hotels were stratified into primary and support departments and systematic random sampling was used to select the respondents. Primary data was gathered from employees by use of self-administered questionnaires while secondary data was gathered from relevant books, hotel records, journal, publications and the internet. Reliability of data was tested using Cronbach’s Alpha resulting in a value above 0.7. Factor analysis was used for data reduction while multiple regression was used to analyze relationships between innovation barriers and proactive work behaviour. ANOVA test was conducted to test the differences in proactive work behavior between male employees and their female counterparts. The findings of this study indicated a relationship between endogenous innovation barriers and proactive work behavior (t=-5.036, p<.000). Besides, there is a relationship between exogenous innovation barriers and proactive work behaviour (t=3.503, p<.0.01). There is no difference in proactive work behaviour between male employees and female employees (F 1.312; p. = 0.269). It was concluded that both endogenous and exogenous innovation barriers may affect proactive behaviour at work place. It is recommended that hotels should focus on creating an enabling work environment that promotes proactive work behavior through provision of adequate resources and embracing leadership style of management. Besides, organisations should embrace gender diversity at workplace to create broader search base for proactive work behaviour
Keywords: Proactive work behaviours; Innovation barriers